Body Composition in Adult Patients with Thalassemia Major - Marianna Vlychou; Evangelos Alexiou; Paschalis Thriskos; Ioannis Fezoulidis; Katerina Vassiou (International Journal of Endocrinology)
Objective. To assess body composition in adult male and female patients with thalassemia major by dual-energy X-ray absorptiometry (DXA) and to compare the findings with a group of healthy age-matched controls. Methods. Our study group included sixty-two patients (27 males, mean age 36 years, and 35 females, mean age 36.4 years) and fifteen age-matched healthy controls. All patients had an established diagnosis of thalassemia major and followed a regular blood transfusion scheme since childhood and chelation treatment. Fat, lean, and bone mineral density (BMD) were assessed with dual-energy X-ray absorptiometry. Ferritin levels and body mass index of all patients and controls were also recorded. Student t-test and Wilcoxon test were performed and statistical significance was set at p<0.05. Results. BMD and whole body lean mass are lower in both male and female adult patients compared with controls (p<0.01 in both groups), whereas whole body fat mass was found to have no statistically significant difference compared to controls. Regional trunk fat around the abdomen was found to be lower in male patients compared to controls (p=0.02). Conclusion. Severe bone loss and diminished lean mass are expected in adult male and female patients with thalassemia major. Fat changes seem to affect mainly male patients.